Long-term effect of intravitreal triamcinolone in the nonproliferative stage of type II idiopathic parafoveal telangiectasia (2008)
PURPOSE: To report the visual outcomes and ocular complications of intravitreal triamcinolone acetonide (IVTA) in the treatment of the nonproliferative stage of type II idiopathic parafoveal telangiectasia (IPT). METHODS: Retrospective, multicenter, uncontrolled interventional case series of 19 eyes of 14 consecutive patients with the nonproliferative stage of IPT that had undergone at least one intravitreal injection of 4 mg of triamcinolone acetonide. Demographic, medical, and ocular data were obtained through chart review. The main outcome measures included best-corrected visual acuity at several timepoints of follow up and ocular complications. RESULTS: At baseline the mean logMAR visual acuity was 0.83 ± 0.41 (Snellen 20/135, range 0.3-2). After an average follow-up of 21.2 months (range 6-44 months), the mean logMAR visual acuity remained essentially unchanged from baseline. At 3 months, the logMAR visual acuity was 0.86 ± 0.44 (Snellen 20/145, P = 0.8378), at 6 months 0.86 ± 0.42 (Snellen 20/145, P = 0.8149), at 12 months 0.87 ± 0.46 (Snellen 20/148, P > 0.9999), at 18 months 0.84 ± 0.35 (Snellen 20/138, P = 0.8385), and at the last follow-up 0.82 ± 0.44 (Snellen 20/132, P = 0.9301). Seven eyes were reinjected once. Ten of 19 eyes (53%) developed cataract (3 eyes underwent phacoemulsification and intraocular lens implantation) and 7 of 19 eyes (37%) had an elevated intraocular pressure, none of which required surgical treatment. CONCLUSION: IVTA does not seem to improve visual acuity in most eyes with the nonproliferative stage of IPT. © The Ophthalmic Communications Society, Inc.